Enhancing Preschool Children’s Language through Physical Education - Goti, Ευθυμία; Derri, Βασιλική; Kioumourtzoglou, Ευθύμης (Inquiries in Physical Education and Sport, 2006)
The aim of this study was to investigate the effect of an integrated physical education and language program in enhancing preschool children’s knowledge on oral and written speech that is related with movement concepts, movement skills, and everyday skills. Sixty seven (34 girls and 33 boys) preschool children, 4 to 6 years of age, were randomly divided into two groups (experimental – control). The experimental group participated in a 5-week integrated teaching program, 4 times per week for 40 minutes whereas the control group followed the typical preschool program. For the assessment of children’s knowledge on oral and written speech, a special instrument with 19 language tasks was constructed. The results showed that children in the experimental group improved the language elements after the application of the program. It can be concluded that an integrated physical education and language program could be successfully applied for the development of language skills in preschool children.